Liprin-α4 is required for nickel induced receptor protein tyrosine phosphatase-leukocyte antigen related receptor F (RPTP-LAR) activity. - Kathrin Kiok (Public Library of Science (PLoS), 2011)
Liprin-α4 was strongly induced following nickel (II) chloride exposure in a variety of cell types including BEAS-2B, A549, BEP2D and BL41 cells. Liprin-α4, a member of the Liprin alpha family, has seven isoforms but only three of these variants were detected in BEAS-2B cells (004, 201 and 202). The level of Liprin-α4 variants 201 and 004 were highly increased in BEAS-2B cells in response to nickel. We showed that Liprin-α4 bound directly to the cytoplasmic region of RPTP-LAR (receptor protein tyrosine phosphatase-leukocyte antigen-related receptor F). The cytoplasmic region of RPTP-LAR contains two phosphatase domains but only the first domain shows activity. The second domain interacts with other proteins. The phosphatase activity was increased both following nickel treatment and also in the presence of nickel ions in cell extracts. Liprin-α4 knock-down lines with decreased expression of Liprin-α4 variants 004 and 201 exhibited greater nickel toxicity compared to controls. The RPTP-LAR phosphatase activity was only slightly increased in a Liprin-α4 knock-down line. Liprin-α4 appeared necessary for the nickel induced tyrosine phosphatase activity. The presence of Liprin-α4 and nickel increased tyrosine phosphatase activity that reduced the global levels of tyrosine phosphorylation in the cell.